2014
DOI: 10.4103/0976-9668.136183
|View full text |Cite
|
Sign up to set email alerts
|

Root conditioning in periodontology - Revisited

Abstract: Objective:Root surfaces of periodontitis-affected teeth are hypermineralized and contaminated with cytotoxic and other biologically active substances. To achieve complete decontamination of the tooth surfaces, various methods including root conditioning following scaling and root planning are present. The main objective of this article is to throw light on the different root conditioning agents used and the goals accomplished by root conditioning in the field of periodontology.Materials and Methods:20 human ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
11
0
3
Order By: Relevance
“…From the Figure 5b, we can see that the S.l-AgNPs have the average diameter of 27 nm, which is much smaller than that of the previously reported papers. [10,11] 3.6 | Electrochemical characteristics of S. l-AgNPs…”
Section: Afm and Tem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From the Figure 5b, we can see that the S.l-AgNPs have the average diameter of 27 nm, which is much smaller than that of the previously reported papers. [10,11] 3.6 | Electrochemical characteristics of S. l-AgNPs…”
Section: Afm and Tem Analysismentioning
confidence: 99%
“…[10] The uses of the microorganisms to the green synthesis of silver nanoparticles also reported. AgNPs have been synthesized by bacteria of Staphylococcus aureus [11] and Bacillus megaterium. [12] In addition, extracellular synthesis of AgNPs have been carried out using fungus of Aspergillus clavatus.…”
mentioning
confidence: 99%
“…Several studies demonstrated the influence of SRP combined with various conditioning agents, such as citric acid, EDTA or tetracycline hydrochlorite on smear layer removal, diameter alteration of dentinal tubules and on the dentin collagen matrix using SEM approach (16,17). These results indicate that root conditioning after SRP is favourable for smear layer removal as well as in exposing the collagen matrix (18).…”
Section: Discussionmentioning
confidence: 98%
“…This may ultimately achieve an optimal degree of demineralization within a short period of time, in comparison to other application modes. 18 Results of this study are discussed below on the percentage of smear layer and the collagen structure exposed cementum. Control group showed there is no apparent effect on the smear layer after scaling and water irrigation.…”
Section: Discussionmentioning
confidence: 99%